SISTEM INFORMASI MANAJEMEN ADMINISTRASI DAN KEUANGAN PADA TK-IT PERMATA HATI SUMBERREJO-BOJONEGORO - Salwa Shofia; Dimas Aryo Anggoro (LPPM Nusa Mandiri, 2020)
Administrative and financial information systems are one of the most widely applied information technologies to facilitate the management of various data into information. TK-IT Permata Hati Sumberrejo still uses manual methods to manage data student, teacher, and staff data as well as recap payment. Data processing is using Microsoft Excel, which results in time-consuming when entering data and when re-doing data correction before reported. This system was developed aiming to help data and financial management to be more effective and efficient. The information from the data entered can be conveyed properly. Therefore, it is necessary to develop a web-based administrative and financial management information system using PHP programming language with Laravel framework. This system designed using the waterfall method. Then the system will be evaluated using the Black Box and User Acceptance Test. The results of this study are an information system with various features that can be used to manage student, teacher, and staff data, as well as to manage recap payments of tuition fees, POMG, uniforms, and activities. The results of the system testing by the Principal, Treasurer, Administrative, and Admin staff can be concluded that the system is running well and meets the needs of the school.